2010
DOI: 10.1029/2009ja014415
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional hybrid simulation of magnetosheath reconnection under northward and southward interplanetary magnetic field

Abstract: [1] A three-dimensional (3-D) global hybrid simulation is carried out for the generation and structure of magnetic reconnection in the magnetosheath because of the interaction of an interplanetary tangential discontinuity (TD) with the bow shock and magnetosphere. Runs are performed for solar wind TDs possessing different polarization senses of magnetic field (north-to-south or south-to-north from the leading to trailing side of the incident TD) and initial half-widths. Two-step compression processes are shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 34 publications
6
24
0
1
Order By: Relevance
“…Both of these changes are favorable for the onset of reconnection. The observations thus suggest that reconnection was initiated near the magnetopause as the result of strong compression of the magnetosheath current sheet against the low-shear magnetopause, in agreement with the simulation results of Pang et al [2010].…”
Section: Summary and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both of these changes are favorable for the onset of reconnection. The observations thus suggest that reconnection was initiated near the magnetopause as the result of strong compression of the magnetosheath current sheet against the low-shear magnetopause, in agreement with the simulation results of Pang et al [2010].…”
Section: Summary and Discussionsupporting
confidence: 90%
“…However, it could not be determined in that study whether it was the compression across the bow shock or the compression against the magnetopause that was more significant for triggering reconnection. Recent 2D and 3D global hybrid simulations suggest that while the bow shock does compress solar wind TDs, compression across the bow shock alone would be insufficient to initiate reconnection in originally thick solar wind TDs and additional compression against the magnetopause would be required [Omidi et al, 2009;Pang et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Using Cluster spacecraft observations, Phan et al (, ) and Hasegawa et al () have identified the initiation of magnetosheath reconnection due to compression of a solar wind current sheet at the bow shock and against the dayside magnetopause. The observation event of Phan et al () has been simulated by performing a two‐dimensional (2‐D; Omidi et al, ) and a three‐dimensional (3‐D) global hybrid simulation (Pang et al, ) for the generation and structure of magnetosheath reconnection due to the interaction between an interplanetary TD and the Q‐ bow shock.…”
Section: Introductionmentioning
confidence: 99%
“…Using Cluster data these authors showed that thin current sheets with typical scales of a few ion inertial lengths (∼100 km) are found downstream of the quasi-parallel shock, and that reconnection can occur at them. Furthermore, observations reported by Phan et al (2007) and simulations by Pang et al (2010) have given evidence that reconnection jets can occur in the magnetosheath due to the compression of solar wind current sheets at the bow shock. More work is needed, however, to determine if reconnection at these sheets can be related to the magnetosheath jets discussed herein.…”
Section: Other Possible Jet Originsmentioning
confidence: 99%